Epoxy resin composition, preparation method and epoxy glass cloth laminated board

By introducing hydroxyl-containing silicone and 4,4'-bismaleimide diphenylmethane into the epoxy resin to form a cross-linked structure, the shortcomings of epoxy resin in terms of toughness and heat resistance are solved, and higher impact and high temperature resistance are achieved.

CN119529476APending Publication Date: 2025-02-28SHENZHEN XIONGYIHUA PLASTIC INSULATION LTD

Patent Information

Application Number
CN202411821085.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Epoxy resins have shortcomings in toughness and heat resistance, resulting in poor performance in applications requiring high impact resistance and high temperature resistance.

Method used

By introducing hydroxyl-containing silicone and 4,4'-bismaleimide diphenylmethane crosslinking with epoxy resin, a new epoxy resin composition is formed, which improves its heat resistance and toughness.

Benefits of technology

The heat resistance and toughness of the epoxy resin composition are improved, and are suitable for many fields such as machinery, electronics, aerospace, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CM1XMVA5IQDE2SL2SBRIZWOXPPXGANPKOZHTQHVL
    Figure CM1XMVA5IQDE2SL2SBRIZWOXPPXGANPKOZHTQHVL
  • Figure GHYC81IWL41F49PVWC0EA191OFKQKNEHIJ7VXHUM
    Figure GHYC81IWL41F49PVWC0EA191OFKQKNEHIJ7VXHUM
  • Figure SRDQZL8LGNLZ4S0NEIKWC17RFOTXQQHHJFSKAHXP
    Figure SRDQZL8LGNLZ4S0NEIKWC17RFOTXQQHHJFSKAHXP
Patent Text Reader

Abstract

The invention relates to the technical field of epoxy resin composite materials, and particularly discloses an epoxy resin composition, a preparation method and an epoxy glass cloth laminated board. The epoxy resin composition is prepared from the following components in parts by weight: 100 parts of epoxy resin, 10 to 20 parts of hydroxyl-containing organic silicon, 3 to 8 parts of maleic anhydride, 0.5 to 2 parts of vinylidene compound, 5 to 15 parts of 4, 4 '-bismaleimide diphenylmethane and 30 to 60 parts of curing agent. The hydroxyl-containing organic silicon and the 4, 4 '-bismaleimide diphenylmethane are crosslinked with the epoxy resin, so that the heat resistance of the epoxy resin is improved, and the toughening effect on the epoxy resin is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of epoxy resin composite materials, and more specifically, to an epoxy resin composition, a preparation method and an epoxy glass cloth laminate. Background Art

[0002] As an important type of thermosetting resin, epoxy resin has been widely used in many fields such as machinery, electronics, aerospace, civil engineering, etc. due to its excellent physical and mechanical properties, electrical insulation properties and good adhesion. Especially in the field of composite materials, epoxy resin as a matrix resin combined with reinforcing materials such as glass fiber and carbon fiber can prepare structural materials with excellent performance. However, despite the many advantages of epoxy resin, it still faces some technical challenges in practical applications, the most notable of which is the lack of toughness and heat resistance.

[0003] As a brittle material, epoxy resin is prone to fracture or crack propagation due to its inherent molecular structure when subjected to external forces, which severely limits its application in situations requiring high impact resistance and resistance to delamination damage. In the field of composite materials, the addition of reinforcing materials such as glass fiber and carbon fiber can significantly improve the overall strength and stiffness of the material, but if the toughness of the matrix resin is insufficient, it is still difficult to effectively resist impact loads and dynamic fatigue damage, thus affecting the overall performance and service life of the composite material.

[0004] With the continuous advancement of science and technology and the rapid development of the industrial field, the requirements for the stability and reliability of materials in high temperature environments are becoming higher and higher. However, traditional epoxy resins are prone to thermal degradation and oxidation reactions under high temperature conditions, resulting in a sharp decline in material performance or even failure. This problem is particularly prominent in the fields of aerospace, automotive engines, high-temperature electronic equipment, etc., because these applications often need to operate in extreme high temperature environments. Therefore, improving the heat resistance of epoxy resins has become a technical problem that needs to be solved urgently.

[0005] In order to solve the shortcomings of epoxy resin in toughness and heat resistance, researchers have conducted a lot of research and experiments. In terms of toughness improvement, researchers have tried to enhance the toughness of epoxy resin by introducing modifiers such as toughening agents, nanoparticles, and rubber phases. These modifiers can form an effective energy dissipation mechanism in the epoxy resin matrix, absorb and disperse impact energy, thereby slowing down the propagation rate of cracks and improving the impact resistance of the material. In addition, through molecular design methods, such as synthesizing epoxy resins with flexible segments or introducing interpenetrating network structures, the toughness of epoxy resins can also be improved to a certain extent.

[0006] In terms of enhancing heat resistance, researchers mainly achieve this by optimizing the curing system, selecting high-temperature resistant curing agents, and adjusting the content of heat-resistant groups in the molecular structure. High-temperature resistant curing agents such as phenolic resins and polyimides can form a more stable cross-linked network structure with epoxy resins, improving the thermal stability and heat resistance of the material. At the same time, the heat resistance of epoxy resins can be further improved by introducing high-temperature resistant functional groups or segments, such as aromatic structures and silicon-oxygen bonds.

[0007] However, these existing solutions often have problems such as high cost, complex process, and impact on other properties, and are difficult to fully meet the needs of practical applications. Therefore, it is particularly important to develop an epoxy resin composition with both good toughness and excellent heat resistance. Summary of the invention

[0008] In order to solve the above technical problems, the present application provides an epoxy resin composition, a preparation method and an epoxy glass cloth laminate. The present application uses hydroxyl-containing silicone and 4,4'-bismaleimide diphenylmethane to cross-link with epoxy resin to improve its heat resistance and achieve a toughening effect on epoxy resin.

[0009] In a first aspect, the present application provides an epoxy resin composition, comprising the following components in parts by weight: 100 parts of epoxy resin, 10-20 parts of hydroxyl-containing silicone, 3-8 parts of maleic anhydride, 0.5-2 parts of vinylidene compound, 5-15 parts of 4,4'-bismaleimide diphenylmethane, and 30-60 parts of curing agent.

[0010] The present application utilizes the Si—O bond in organic silicon to improve the toughness of the epoxy resin curing system, and utilizes the rigid groups such as the benzene ring and amide group in 4,4'-bismaleimide diphenylmethane to improve the strength and heat resistance of the epoxy resin curing system.

[0011] The present application utilizes maleic anhydride to graft-modify hydroxy silicone to generate silicone containing carboxyl groups, so as to improve the compatibility between silicone and epoxy resin; in addition, the present application uses vinylidene-containing olefins and maleic anhydride for pericyclic grafting to introduce flexible long chain branches into the epoxy resin, thereby improving the mobility of the epoxy resin, alleviating the internal stress concentration effect when subjected to external forces, and giving the epoxy resin curing system high toughness.

[0012] Furthermore, the hydroxyl-containing silicone is silanol or hydroxyl silicone oil.

[0013] The silanols include but are not limited to trimethylsilanol, tri(tert-pentaoxy)silanol, dimethylphenylsilanol, etc.; the hydroxy silicone oils include but are not limited to hydroxy-terminated polymethylsiloxane, hydroxy-terminated polymethylphenylsiloxane, hydroxy-terminated phenylsiloxane, etc.

[0014] Furthermore, the vinylidene compound has 14-30 carbon atoms.

[0015] The vinylidene compound is an oligomer of alpha olefins, and the alpha olefins include but are not limited to 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, and the oligomer is a dimer, trimer, tetramer or pentamer.

[0016] Furthermore, the curing agent is an amine curing agent or an acid anhydride curing agent.

[0017] The amine curing agent includes but is not limited to dicyandiamide, 4,4-diaminodiphenyl sulfone, diaminodiphenylmethane, diaminodiphenyl ether, meta-phenylenediamine, meta-phenylenediamine, ethylenediamine, polyethyleneamine, polyamide, benzidine, etc.; the anhydride curing agent includes but is not limited to maleic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, tetrabromophthalic anhydride, etc.

[0018] Furthermore, under the premise of not affecting the performance of the epoxy resin composition, a curing accelerator may be appropriately added to shorten the curing time of the epoxy resin composition. The curing accelerator is selected from at least one of a phenolic accelerator, an imidazole accelerator, and an amine accelerator.

[0019] The phenolic accelerators include but are not limited to phenol, resorcinol, nonylphenol, bisphenol A, etc.; the imidazole accelerators include but are not limited to 2-methylimidazole, 2-phenylimidazole, etc.; the amine accelerators include but are not limited to triethylamine, triethanolamine, benzyldimethylamine, o-hydroxybenzyldimethylamine, etc.

[0020] Furthermore, considering the promotion effect, compared with the total weight of the epoxy resin composition, the addition amount of the curing accelerator of the present application is 0.05-2%, preferably 0.1-1%.

[0021] In a second aspect, the present application provides a method for preparing an epoxy resin composition, using the following technical solution: A method for preparing an epoxy resin composition comprises the following steps: S1, mixing maleic anhydride and a vinylidene compound, heating the mixture for reaction for 8-10 hours, filtering, evaporating and concentrating, and distilling under reduced pressure in sequence to obtain a vinylidene grafted anhydride product; S2, mixing epoxy resin, hydroxyl-containing organosilicon, and vinylidene graft anhydride product, heating for reaction for 4-8 hours, and distilling under reduced pressure to obtain organosilicon-modified epoxy resin; S3, mixing the organosilicon-modified epoxy resin and 4,4'-bismaleimide diphenylmethane, heating to react for 4-8 hours, cooling, adding a curing agent, and stirring evenly to obtain an epoxy resin composition.

[0022] Maleic anhydride is open-ring grafted onto silicone to introduce carboxyl groups with strong polarity, thereby increasing the polarity of silicone molecules and thus increasing their compatibility with epoxy resins. Without the need for the catalytic action of silane coupling agents, the epoxy resin can be modified by reacting the active groups of silicone such as hydroxyl and carboxyl alkoxy with the epoxy and hydroxyl groups of epoxy resins.

[0023] The poly-alpha-olefin grafted maleic anhydride compound can be used in excess. The poly-alpha-olefin grafted maleic anhydride compound that has not reacted with the hydroxyl-containing resin can also react with the epoxy group of the epoxy resin to improve its toughness because it contains anhydride active groups.

[0024] Furthermore, in step S1, the heating temperature is 160-180°C, preferably 170°C.

[0025] Furthermore, in step S2, the heating temperature is 90-100°C, preferably 95°C.

[0026] Furthermore, in step S3, the heating temperature is 130-140°C, preferably 130°C.

[0027] In a third aspect, the present application provides an epoxy glass cloth laminate, which adopts the following technical solution: An epoxy glass cloth laminate is prepared from glass fiber cloth and the epoxy resin composition provided in the second aspect.

[0028] In a fourth aspect, the present application provides a method for preparing an epoxy glass cloth laminate, which adopts the following technical solution: An epoxy glass cloth laminate comprises the following steps: Cut fiberglass cloth according to certain specifications, stack multiple layers of fiberglass cloth on a glass plate, evenly coat the epoxy resin composition on the fiberglass cloth, and allow the epoxy resin composition to penetrate the fiberglass cloth to obtain an epoxy resin / fiberglass composite material. Then, place the obtained composite material in an oven and dry it for 2-4 hours. Place the dried composite material between the upper and lower molds of a laminator, start lamination, cool and demold after lamination, and obtain an epoxy glass cloth laminate.

[0029] Furthermore, the epoxy resin / glass fiber composite material has a glue content of 40-50%, preferably 42%.

[0030] Furthermore, the drying temperature of the epoxy resin / glass fiber composite material in the oven is 80-100°C, preferably 100°C.

[0031] Furthermore, the laminating steps of the epoxy resin / glass fiber composite material in the laminator are as follows: placing the dried composite material between the upper and lower molds of the laminator, starting the laminator, setting the temperatures of the upper and lower molds to 80°C, and maintaining a template contact pressure of 2MPa, and after the temperature reaches 80°C, changing the template contact pressure to 10MPa, then raising the temperature to 150°C and keeping the pressure unchanged for 2h, then raising the temperature to 170°C and keeping it for 2h, and finally keeping it at 235°C for 1h, and demolding after cooling to obtain the epoxy glass cloth laminate.

[0032] In summary, this application has the following beneficial effects: The present application introduces hydroxyl-containing organosilicon and 4,4'-bismaleimide diphenylmethane to cross-link with epoxy resin to improve its heat resistance and achieve a toughening effect. The composition provided in the present application includes components such as epoxy resin, hydroxyl-containing organosilicon, maleic anhydride, vinylidene compound, 4,4'-bismaleimide diphenylmethane and curing agent, and finally obtains an epoxy resin composition through a specific preparation method, including the reaction of maleic anhydride and vinylidene compound, the preparation of organosilicon-modified epoxy resin and the mixing with 4,4'-bismaleimide diphenylmethane. In addition, a method for preparing an epoxy glass cloth laminate is provided, which includes the steps of cutting glass fiber cloth, coating epoxy resin composition, drying and laminating. The obtained epoxy glass cloth laminate has good toughness and excellent heat resistance, and is suitable for multiple fields, such as machinery, electronics, aerospace, etc. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] Sources of some raw material components in this application: The epoxy resin adopts bisphenol A epoxy resin, model EP01441-310; 4,4′-Bismaleimidodiphenylmethane was purchased from Nanjing Bermuda Biotechnology Co., Ltd.; Hydroxyl-terminated polydimethylsiloxane, purchased from Wengjiang Chemical, Mn = 1000; Hydroxyl-terminated diphenyl polysiloxane, purchased from Wengjiang Chemical, product number PB91704; The polydecene used was Durasyn 162 produced by British Petroleum, which was composed of 85% decene dimer and 15% decene trimer; Glass fiber cloth was purchased from Shandong Chengguan New Materials Co., Ltd., model 7637, warp yarn ECG751 / 0, weft yarn ECG371 / 0, thickness 0.210±0.02mm.

[0035] Example 1-5 Epoxy resin composition: Epoxy resin EP01441-310 was used as the main resin, 4,4-diaminodiphenyl sulfone (DDS) was used as the curing agent, 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) was used as the curing accelerator, hydroxyl-terminated polydimethylsiloxane and hydroxyl-terminated diphenylpolysiloxane were used as hydroxyl-containing silicones, and polydecene Durasyn 162 was used as the vinylidene compound to prepare an epoxy resin composition. The amounts of the formula components are shown in Table 1.

[0036] Preparation steps: S1, adding maleic anhydride and polydecene Durasyn 162 into a reaction kettle, mixing and stirring evenly, heating to 170°C, reacting for 10 hours, filtering, evaporating and concentrating, and distilling under reduced pressure in sequence to obtain a vinylidene grafted anhydride product; S2, adding epoxy resin EP01441-310, hydroxyl-containing organosilicon, and the vinylidene graft anhydride product obtained in step S1 into a reaction kettle, mixing and stirring evenly, heating to 95° C., reacting for 6 hours, and distilling under reduced pressure to obtain organosilicon-modified epoxy resin; S3, adding the organosilicon-modified epoxy resin and 4,4'-bismaleimide diphenylmethane obtained in step S2 into a reaction kettle, mixing and stirring evenly, heating to 130° C., reacting for 6 hours, cooling to room temperature, adding curing agent DDS and curing accelerator DMP-30, stirring evenly, and obtaining an epoxy resin composition.

[0037] Table 1 (Unit: kg) Comparative Example 1 Epoxy resin composition: The difference from Example 1 is that the maleic anhydride is not modified by using polydecene Durasyn 162. The dosage of the formula components is shown in Table 1.

[0038] Preparation steps: S1, adding epoxy resin EP01441-310, hydroxyl-containing silicone and maleic anhydride into a reaction kettle, mixing and stirring evenly, heating to 95° C., reacting for 6 hours, and distilling under reduced pressure to obtain silicone-modified epoxy resin; S2, adding the organosilicon-modified epoxy resin and 4,4'-bismaleimide diphenylmethane obtained in step S2 into a reaction kettle, mixing and stirring evenly, heating to 130° C., reacting for 6 hours, cooling to room temperature, adding curing agent DDS and curing accelerator DMP-30, stirring evenly, and obtaining an epoxy resin composition.

[0039] Comparative Example 2 Epoxy resin composition: The difference from Example 1 is that no vinylidene compound is added to graft maleic anhydride, and a catalyst dibutyltin dilaurate is added during the modification of the epoxy resin with hydroxyl-containing silicone. The amounts of the formula components are shown in Table 1.

[0040] Preparation steps: S1, adding epoxy resin EP01441-310, hydroxyl-containing silicone and dibutyltin dilaurate into a reaction kettle, mixing and stirring evenly, heating to 95° C., reacting for 6 hours, and distilling under reduced pressure to obtain silicone-modified epoxy resin; S2, adding the organosilicon-modified epoxy resin and 4,4'-bismaleimide diphenylmethane obtained in step S2 into a reaction kettle, mixing and stirring evenly, heating to 130° C., reacting for 6 hours, cooling to room temperature, adding curing agent DDS and curing accelerator DMP-30, stirring evenly, and obtaining an epoxy resin composition.

[0041] Comparative Example 3 Epoxy resin composition: The difference from Example 1 is that the same amount of acetic anhydride is used to replace maleic anhydride, and the preparation steps are the same as those of Example 1.

[0042] Heat resistance test of epoxy resin composition: The epoxy resin composition was characterized by its 5% weight loss temperature in a N2 atmosphere and its residual weight at 900°C after curing. The test results are recorded in Table 2.

[0043] Table 2 It can be seen from the test results in Table 2 that the epoxy resin composition prepared in the present application has excellent heat resistance, with a 5% thermal weight loss temperature of 440-463°C and a residual weight of 48.4-59.7% at 900°C. In addition, in the process of using silicone-modified epoxy resin in the present application, vinylidene grafted maleic anhydride-modified hydroxy silicone is used instead of directly adding a catalyst, which can effectively shorten the surface drying time and actual drying time of the epoxy resin composition.

[0044] Epoxy glass cloth laminate: Epoxy glass laminates were prepared using glass fiber cloth as a substrate and the epoxy resin compositions prepared in Examples 1-5 and Comparative Examples 1-3 as a binder.

[0045] Preparation steps: The glass fiber cloth is cut into a size of 100mm×100mm, 10 layers of glass fiber cloth are stacked on a glass plate, and the epoxy resin composition is evenly coated on the glass fiber cloth, so that the epoxy resin composition penetrates the glass fiber cloth to obtain an epoxy resin / glass fiber composite material (containing 42% glue), and then the obtained composite material is placed in an oven and dried at 100°C for 2h, and the dried composite material is placed between the upper and lower molds of a laminator, and the laminator is turned on, and the upper and lower mold temperatures are set to 80°C, and the template contact pressure is maintained at 2MPa. After the temperature reaches 80°C, the template contact pressure is changed to 10MPa, and then the temperature is raised to 150°C, the pressure is kept unchanged, and the temperature is kept for 2h, and then the temperature is raised to 170°C and kept for 2h, and finally kept at 235°C for 1h, and demolded after cooling to obtain an epoxy glass cloth laminate.

[0046] Mechanical properties test of epoxy glass cloth laminate: The mechanical properties of the epoxy glass cloth laminate, such as toughness, were characterized by the flexural strength and notched impact strength at 180°C±3°C. The test results are recorded in Table 3.

[0047] Table 3 As shown in Table 3, the epoxy glass laminate prepared in this application has a bending strength of 361-401 MPa at 180°C and a notched impact strength of 295-335 KJ / m 2 , with excellent toughness and strength.

[0048] Comparison of Example 1 and Comparative Example 1 shows that the laminate of Comparative Example 1 has a 180°C flexural strength of 306 MPa and a notched impact strength of 204 KJ / m without grafting maleic anhydride with vinylidene compounds. 2 , the toughness and strength decreased significantly, indicating that the introduction of side long chains can improve the mobility and stress relief effect of epoxy resin polymers, thereby improving the toughness and strength of the laminate.

[0049] By comparing Example 1 and Comparative Example 2, it can be seen that dibutyltin dilaurate is used instead of maleic anhydride to improve the compatibility between silicone and epoxy resin. The mechanical properties of Comparative Example 2 show relatively poor test results. This may be because maleic anhydride not only introduces long side chains to the epoxy resin polymer to improve its mobility, but also maleic anhydride can participate in the later curing of the epoxy resin and improve the curing crosslinking degree of the epoxy resin.

[0050] By comparing Example 1 and Comparative Example 3, it can be seen that the strength of the laminate is significantly reduced by using acetic anhydride instead of maleic anhydride. Combined with Table 2, the heat resistance of the epoxy resin composition after curing is also significantly reduced. It is speculated that this may be because after acetic anhydride is grafted with hydroxy silicone, it is completely esterified and there is no residual carboxyl group, resulting in no effective improvement in the compatibility between silicone and epoxy resin.

[0051] The above is only the preferred implementation of the present application. The protection scope of the present application is not limited to the above embodiments. All technical solutions under the concept of the present application belong to the protection scope of the present application. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present application should also be regarded as the protection scope of the present application.

Claims

1. An epoxy resin composition, characterized in that The invention comprises the following components in parts by weight: 100 parts of epoxy resin, 10-20 parts of hydroxyl-containing organic silicon, 3-8 parts of maleic anhydride, 0.5-2 parts of vinylidene compound, 5-15 parts of 4,4'-bismaleimide diphenylmethane and 30-60 parts of curing agent.

2. The epoxy resin composition according to claim 1, characterized in that The hydroxyl-containing organic silicon is silanol or hydroxyl silicone oil.

3. The epoxy resin composition according to claim 2, characterized in that The silanol includes at least one of trimethylsilanol, tri(tert-pentaoxy)silanol, and dimethylphenylsilanol, and the hydroxy silicone oil includes at least one of hydroxy-terminated polymethylsiloxane, hydroxy-terminated polymethylphenylsiloxane, and hydroxy-terminated phenylsiloxane.

4. The epoxy resin composition according to claim 1, characterized in that The vinylidene compound has 14-30 carbon atoms.

5. The epoxy resin composition according to claim 4, characterized in that The vinylidene compound is an oligomer of alpha olefins, and the alpha olefins include 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, and 1-pentadecene, and the oligomer is at least one of a dimer, a trimer, a tetramer, and a pentamer.

6. The epoxy resin composition according to claim 1, characterized in that The curing agent is an amine curing agent or an acid anhydride curing agent. The amine curing agent includes dicyandiamide, 4,4-diaminodiphenyl sulfone, diaminodiphenylmethane, diaminodiphenyl ether, metaphenylenediamine, metaphenylenediamine, ethylenediamine, polyethyleneamine, polyamide, benzidine, etc.; the acid anhydride curing agent includes but is not limited to at least one of maleic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, and tetrabromophthalic anhydride.

7. The epoxy resin composition according to claim 1, characterized in that The epoxy resin composition further comprises 0.05-2% of a curing accelerator based on the total weight of the epoxy resin composition. The curing accelerator is selected from at least one of a phenolic accelerator, an imidazole accelerator and an amine accelerator.

8. A method for preparing the epoxy resin composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing maleic anhydride and a vinylidene compound, heating the mixture for reaction for 8-10 hours, filtering, evaporating and concentrating, and distilling under reduced pressure in sequence to obtain a vinylidene grafted anhydride product; S2, mixing epoxy resin, hydroxyl-containing organosilicon, and vinylidene graft anhydride product, heating for reaction for 4-8 hours, and distilling under reduced pressure to obtain organosilicon-modified epoxy resin; S3, mixing the organosilicon-modified epoxy resin and 4,4'-bismaleimide diphenylmethane, heating to react for 4-8 hours, cooling, adding a curing agent, and stirring evenly to obtain an epoxy resin composition.

9. An epoxy glass cloth laminate, characterized in that: The epoxy glass cloth laminate is prepared by laminating glass fiber cloth and the epoxy resin composition according to any one of claims 1 to 7.

10. The epoxy glass cloth laminate according to claim 9, characterized in that: The epoxy glass cloth laminate is prepared by the following preparation steps: cutting fiber glass cloth, stacking multiple layers of glass fiber cloth on a glass plate, uniformly coating the epoxy resin composition on the glass fiber cloth, allowing the epoxy resin composition to penetrate the glass fiber cloth to obtain an epoxy resin / glass fiber composite material, then placing the obtained composite material in an oven, drying for 2-4 hours, and placing the dried composite material between the upper and lower molds of a laminator, starting lamination, cooling and demoulding after lamination, and obtaining the epoxy glass cloth laminate.

Citation Information

Patent Citations

  • Method for preparing dynamic curing epoxy resin, inorganic filler and polyolefin composite

    CN102002188A

  • Thermosetting resin composition, preparation method thereof and laminate

    CN102504489A

  • Organosilicon-epoxy resin composition and preparation method thereof

    CN102532809A

  • Modified epoxy resin and glass fiber reinforcement plate prepared based on same

    CN107033328A

  • Environmental stress-resistant epoxy resin powder coating and preparation method thereof

    CN108250908A

Cited By

  • Flame-retardant insulating high-performance laminated product and preparation method thereof

    CN120986034A